Treatment of Femur Neck Fracture in Children with Osteogenesis Imperfecta: Two Case Reports. Issue 4 (October 2019) - Morcos, Mina W.; Hamdy, Reggie C.; Fassier, Francois; Saran, Neil
Abstract : Case: We present 2 cases of femoral neck fracture (FNF) in patients with osteogenesis imperfecta (OI) with a previously placed intramedullary nail (IMN). Case 1: A 12-year-old girl who sustained a right FNF after spine surgery. Case 2: An 18-year-old boy who sustained a right FNF after IMN of the left side. Both patients underwent our modified surgical technique as described below. Both patients recovered well overall. Conclusions: FNF in patients with OI poses a significant challenge especially in the presence of an IMN. Here, we describe a surgical technique that provides stable fixation with a less stress riser effect by bypassing the screws and a previously placed nail.